Response of Competition Indices to Row Configuration in Sorghum (Sorghum Bicolor L.)- Mung Bean (Vigna Radiata L.) Intercropping and seed proportion of mung bean in Additive Series in Semi-Arid Area of Wag Hemira Zone, Ethiopia - asres, fentaw (International Journal on Food, Agriculture and Natural Resources, 2025)
Abstract-In the dry land areas, intercropping is the right options in reduce yield reduction due to erratic rainfall distribution. Proper crop combination, optimum plant population and suitable row configuration is of paramount importance in intercropping systems. Sorghum as a main crop and mung bean as supplementary crop is the main cropping system in semi aired area of Wag-hemira zone, Ethiopia. However, the row configuration and seed proportion have never been investigated in Wag-hemira. Thus, an experiment was conducted to determine the optimum level of mung bean seed proportion and proper sorghum mug bean row arrangement for maximum productivity and profitability in additive series intercropping system during 2023 at Aybra. Three seed proportions of mung bean (200%, 100%, and 67%), and four row configurations (1S:1M, 2S:1M, 1S:2M, and 3S:1M) with two sole cropping systems as check in additive series in Randomization block design (RCBD) with three replications in factorial system unsymmetrical way. The collected parameters in both study crops were analysis using SAS software. The land equivalent ratio (LER), competitive ratio (CR), area-time equivalent ratio (ATER), monetary advantage index (MAI) were calculated. The partial budget analysis was carried out after reducing the yield by 10%. The highest total LER (1.39) and MAI (57119, 48971 ETB ha-1) were obtained when 67% of the seed was planted in the 1S:1M row ratio. The highest marginal rate of return (2094.203) was observed when a 200% seed rate of mung bean was planted in a 1S:1M row ratio. Therefore, based on the superior compatibility, and economic benefit, intercropping of sorghum with mung bean in a 1S:1M ratio with 67% seed proportion, followed by 200% seed proportion of mung bean is recommended for the study area and similar agro ecology.Key words- sorghum, Economic benefit, Land equivalent ratio, seed proportions